2020
DOI: 10.1186/s12864-020-07209-2
|View full text |Cite
|
Sign up to set email alerts
|

Changes in transcriptomic and metabolomic profiles of morphotypes of Ophiocordyceps sinensis within the hemocoel of its host larvae, Thitarodes xiaojinensis

Abstract: Background Ophiocordyceps sinensis (Berk.) is a well-known entomopathogenic and medicinal fungus. It parasitizes and mummifies the underground ghost moth larvae to produce a fruiting body named Chinese cordyceps. Specific for the fungus, O. sinensis experiences a biotrophic vegetative growth period spanning over 5 months. During this vegetative growth, it appears successively in the host hemocoel in three/four morphotypes, namely, the yeast-like blastospores (subdivided into proliferative (BP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Additionally, there is a shortage of intermediate compounds and energy caused by the downregulation of succinate. The relatively low carbohydrate content observed in this study can be attributed to the glucose and glucose conjugates that break down maltose being converted into TCA cycle intermediates 41 . Therefore, such changes in sugar levels are expected to affect the generation of energy and intermediate compounds in order to maintain normal biological processes 21 .…”
Section: Discussionmentioning
confidence: 66%
“…Additionally, there is a shortage of intermediate compounds and energy caused by the downregulation of succinate. The relatively low carbohydrate content observed in this study can be attributed to the glucose and glucose conjugates that break down maltose being converted into TCA cycle intermediates 41 . Therefore, such changes in sugar levels are expected to affect the generation of energy and intermediate compounds in order to maintain normal biological processes 21 .…”
Section: Discussionmentioning
confidence: 66%
“…sinensis mainly propagates asexually in the form of hyphal bodies [ 28 ]. At the subsequent stage, the hyphal bodies are induced by certain signal substances to transform by hyphae proliferation [ 29 ]. Our results revealed that, as the content of O .…”
Section: Discussionmentioning
confidence: 99%
“…sinensis in liquid fermentation and host hemolymph was the same, the similar morphological changes can also provide a reference for studying the dimorphic transition of O . sinensis [ 29 ]. Our findings provide a tool for future research on morphogenesis and morphological changes of O .…”
Section: Discussionmentioning
confidence: 99%
“…A few works have focused on development or infection influences. It was revealed that the main life activity metabolism was consistent across O. sinensis morphotypes, but each morphotype adopted a different metabolic pattern [55]. It was observed that metabolic changes of C. militaris could increase and reach maximal after inoculation with germinated soybean during rearing [56].…”
Section: Featured Metabolites and Their Potential Roles As New Quality Control Biomarkersmentioning
confidence: 96%